A novel fluorescent probe with red emission and a large Stokes shift for selective imaging of endogenous cysteine in living cells. Issue 23 (22nd October 2018) - Chen, Dugang; Long, Zi; Dang, Yecheng; Chen, Li
Abstract : A new probeANT selectively mapped endogenous Cys in living cells with bright red-emission and a large Stokes shift. Abstract : Cysteine (Cys) plays crucial roles in physiological and pathological processes, and is related to many diseases. Selective monitoring of Cys over its analogues homocysteine (Hcy) and glutathione (GSH) is of great significance. A probe namedANT with an acrylate group as a recognizing moiety and a red-emission dye with a large Stokes shift (160 nm) as a fluorophore was designed and synthesized. The acrylate group can quench the fluorescence ofANT by a photoinduced electron transfer (PET) process. However, in the presence of Cys, the emission was switched on by the cleavage of the quencher through a concerted reaction including Michael addition and intramolecular cyclization. Furthermore, solution experiments showed thatANT exhibited high sensitivity and selectivity towards Cys with the maximum emission at 640 nm. Besides, ANT was successfully applied to specifically map endogenous Cys in living MCF-7 cells with low toxicity, despite the interference of Hcy and GSH. We hope that such a prepared novel probe will bring advancement in specifically differentiating Cys, Hcy and GSH.